1999
DOI: 10.2337/diacare.22.6.944
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, type 2 diabetes, and insulin resistance in Pima Indian children and young adults.

Abstract: Low-birth-weight Pimas are thinner at ages 5-29 years, yet they are more insulin resistant relative to their body size than those of normal birth weight. By contrast, those with high birth weight are more obese but less insulin resistant relative to their body size. The insulin resistance of low-birth-weight Pima Indians may explain their increased risk for type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
119
1
10

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(151 citation statements)
references
References 10 publications
21
119
1
10
Order By: Relevance
“…Our finding of a possible U-shaped association between birthweight and type 2 diabetes is in agreement with some studies [19,20], but most report an inverse relationship (reviewed in [3]). In agreement with Whincup et al (1997) [21], we found that the post-natal growth effect was stronger than the pre-natal effect indicated by birthweight.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of a possible U-shaped association between birthweight and type 2 diabetes is in agreement with some studies [19,20], but most report an inverse relationship (reviewed in [3]). In agreement with Whincup et al (1997) [21], we found that the post-natal growth effect was stronger than the pre-natal effect indicated by birthweight.…”
Section: Discussionsupporting
confidence: 93%
“…Our study confirms that BMI is a powerful determinant of HOMA%S and HOMA%b, as others have shown [4,7,10]. Our study demonstrates that the association of BMI z-score with low HOMA%S and high HOMA%b may correspond to an increase of HOMA%b which compensates for the low HOMA% S. Previous studies have reported that the effect of BMI on insulin resistance is more consistent and of higher effect size than BW [10,14], as also shown in our study. Results from a study using an animal model have shown that decreased fetal size is associated with beta-cell hyperfunction in early life, which is consistent with our findings [13].…”
Section: Interpretation Of the Findingssupporting
confidence: 91%
“…In our study BW z-score was associated with HOMA%b before and after adjustment for current BMI z-score, but only in Ribeirao Preto. There was no suggestion of a non-linear association between BW and either insulin resistance or secretion in our study, as has been previously suggested [14,29].…”
Section: Interpretation Of the Findingssupporting
confidence: 50%
See 1 more Smart Citation
“…Clinical studies have demonstrated that maternal diabetes increases the offspring's risk of developing type 2 diabetes [11,23,24]. Basic research in animal models of diabetes has shown similar effects [7,25,26].…”
Section: Discussionmentioning
confidence: 99%